Determination Of Seismic Vulnerability Assessment By Using Rapid Screening Method Through Web-Based Application - Ooi, Jun Hao (Universiti Sains Malaysia, 2021)
Rapid Visual Screening is a quick and simple approach often used by researchers to estimate the seismic vulnerability of large number of buildings. Although the results might not be accurate, it no doubt will provide insight to the stakeholders about which part of a study area is generally more vulnerable and requires more attention in future seismic mitigation plan. Although Penang is yet to experience any major earthquake, seismic vulnerability researches should be done as soon as possible to make sure the state is well prepared to face potential near-field and far-field seismic influence in the future. In this study, preliminary seismic vulnerability assessment of 500 buildings situated at northern and eastern George Town, Malaysia was carried out by utilizing modified FEMA-154 (2002) method that suits Malaysian conditions, combining with full online data collection approach via Google Maps and Google Earth. This RVS approach will generate a final performance score for every building based on several governing parameters such as building lateral load resisting system, building height, structural irregularities, building age and soil type, which their respective damage state post-earthquake event can be predicted. The results revealed the immediate need of effective seismic mitigation strategy, as 90% of the studied buildings were considered seismic hazardous and require further detailed analysis to pinpoint their exact seismic vulnerability performance. The considerably bad performance of building stocks might relates to all those aforementioned parameters, thus a GIS map, “RVS Malaysian Form- George Town Area”, was created via ArcGIS platform and shared to the public to provide important information regarding those parameters, which can be used as a foundation for further research work.